2018
DOI: 10.17501/24246735.2018.4102
|View full text |Cite
|
Sign up to set email alerts
|

Abc Strategy: How University Students Perception of Abc Strategy Influences Uptake of Reproductive Health Programs

Abstract: Background: Attitude is what influences all actions an individual undertakes in life. Young adult"s attitude on sexual reproductive health has proven to have a significant influence on their sexual health lifestyle and access to healthcare. Institutions of higher learning have put in place measures to ensure student have access to youth friendly services yet this has not been matched with students utilizing the various reproductive health services within the university. To fully understand students attitude to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The students, therefore, expect career counsellors to adopt innovative methods appropriate in communicating with modern youth and hence improve awareness and utilisation of the services they offer. Wanjau (2011) studied determinants of students' uptake of reproductive health services, and noted that confidentiality was likely to influence the uptake of reproductive health services (Godia et al, 2013). The study found that the information students shared with reproductive health providers in various programmes influenced their uptake of reproductive health services, if it was not kept confidential.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…The students, therefore, expect career counsellors to adopt innovative methods appropriate in communicating with modern youth and hence improve awareness and utilisation of the services they offer. Wanjau (2011) studied determinants of students' uptake of reproductive health services, and noted that confidentiality was likely to influence the uptake of reproductive health services (Godia et al, 2013). The study found that the information students shared with reproductive health providers in various programmes influenced their uptake of reproductive health services, if it was not kept confidential.…”
Section: ____________________________________________________________...mentioning
confidence: 99%